COMMUNICATION BEHAVIOR OF TEACHERS IN DEVELOPING EARLY CHILDHOOD CREATIVITY IN TK AN-NAMIROH 1 PEKANBARU - Ines Asaladiba; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Childhood is a period when an individual tends to follow and absorb everything easier that is seen and felt around, either in the form of attitudes , behaviors , actions , and words that are heard. All of that helps children to develop their creativity. Early childhood is also called the golden age which means  this period can be said as a very important period in the forming creativity of early childhood development for the future. to develop the creativity of early childhood, the communication behavior of teachers becomes the determinant of the creativity of early childhood. The purpose of this research is to determine how verbal communication behaviors of teachers in developing early childhood creativity and how non-verbal communication behaviors of teachers in developing early childhood creativity in the kindergarten An - Namiroh 1, Pekanbaru .This research uses the qualitative descriptive study with the symbolic interaction approach. Data that has been collected by the authors based on the observations and interviews . The informants in this research consist of six people ; which three informants are teachers in the An Namiroh 1 kindergartenin  and the technique used in this research is purposive sampling and another three informants are two students of An-Namiroh 1 kindergarten and the parent, while the datacollection uses the Accidental technique . All data are collected through some interviews , observation of non - participant , documentation and the test for  validity of trangulation.The results of this study show that  verbal communication of teachers in kindergarten An - Namiroh 1 pekanbaru uses a simple and easy Indonesian language to understand to ease the development of childhood creativity . Teachers also use the polite Indonesian so the children get used to it . In addition , using the greeting in English can help the children learn and remember a new language that given. While the non-verbal communication behaviors of teachers in kindergarten An - Namiroh 1 become the contributing factors of verbal communication , because in understanding Jom FISIP Vol. 2 No.1 febuari 2015 2kids in early childhood need some type of communications, that is the visual communication type ( seeing ) , audio communication type( listening ) and audio  –visual communication type ( seeing and listening ) .Keywords : teacher communication behavior , verbal communication , non- verbal communication , symbolic interaction , child creativity